고분자전해질연료전지를 위한 고장 검출 및 진단 기술 - 이원용(Won-yong Lee); 박구곤(Gu-gon Park); 손영준(Young-jun Sohn); 김승곤(Seung-gon Kim); 김민진(Minjin Kim) (한국수소 및 신에너지학회 논문집, 2017)
Fuel cell systems have to satisfy acceptable operating reliability, sufficient lifetime and price to enter the market in competition with existing products. Fuel cells are made up of complex element technologies and various problems related to the failure of the components can affect the reliability and safety of the system. This problem can be overcome by introducing a monitoring and supervisory control system in addition to automatic control to detect the failure of the fuel cell quickly and properly diagnose the performance degradation. For the fault detection and diagnosis of polymer electrolyte fuel cells, the model based method using the theoretical superposition value and the non-model based method of checking the signal tendency or the converted signal characteristic can be applied. The methods analyzed in this paper can contribute to the development of integrated monitoring and control technology for the whole system as well as the stack.